1996
DOI: 10.1172/jci118646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythropoietin on muscle O2 transport during exercise in patients with chronic renal failure.

Abstract: Erythropoietin (rHuEPO) has proven to be effective in the treatment of anemia of chronic renal failure (CRF). Despite improving the quality of life, peak oxygen uptake after rHuEPO therapy is not improved as much as the increase in hemoglobin concentration ([Hb]) would predict. We hypothesized that this discrepancy is due to failure of O 2 transport rates to rise in a manner proportional to [Hb]. To test this, eight patients with CRF undergoing regular hemodialysis were studied pre-and post-rHuEPO ([Hb] ϭ 7.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 31 publications
5
79
0
1
Order By: Relevance
“…In a previous study with CRF patients (10), O 2 supply dependency of O 2 max was demonstrated. This indicates that peak O 2 is not determined by mitochondrial oxidative limits.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In a previous study with CRF patients (10), O 2 supply dependency of O 2 max was demonstrated. This indicates that peak O 2 is not determined by mitochondrial oxidative limits.…”
Section: Introductionmentioning
confidence: 83%
“…This returns elevated muscle blood flow ( ) to values similar to levels seen in matched control subjects during peak exercise and partially offsets the effect of the rise in arterial O 2 content on O 2 delivery. Second, O 2 conductance from muscle microcirculation to mitochondria is particularly low in CRF patients (10) and after rHuEPO therapy still remains at ‫ف‬ 70% of that seen in control subjects. The structural basis of this abnormal O 2 transport conductance is likely microvascular rarification and capillarymyofiber dissociation provoked by a uremic myopathy (11)(12)(13).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other complications in lung tissue are found in patients with CKF, such as pulmonary edema, pleural effusion (mainly in terminal patients with CKF), pulmonary and pleural fibrosis and calcification, pulmonary hypertension, decreased pulmonary capillary blood flow and hypoxemia 13,14 . There are also deficits in oxygen supply to the muscles as a result of decreased peripheral microcirculation, decreased muscle ATP synthesis due to deficiencies in the use of carbohydrates, signs of insulin resistance and changes to glycolytic enzymes, and decreased oxidation of fatty acids [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, maximal oxygen uptake (VO 2 max), the best single indicator of physical working capacity, is decreased. In older adults, a strong inverse association between physical activity and functional decline has been consistently observed [42,57,64,68]. Accordingly, one may expect maximal cardiac output to decrease with aging irrespective of lifestyle due to genetic factors.…”
Section: Introductionmentioning
confidence: 98%